The scorpion's tail [compact disc, unabridged] : a Nora Kelly novel - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J Nora Kelly, 2021)
After a shoot-out Swanson is involved in leaves a senior FBI agent gravely wounded, Corrie finds herself under investigation. Her supervisor assures her she's not to blame and the black mark on her record will be cleared in short order. But Corrie finds herself unable to shake her overwhelming guilt. As a distraction, she takes on a new case involving a fifty-year-old, mummified corpse discovered in a hidden enclave at High Lonesome, a long-abandoned New Mexico ghost town. Quickly out of her depth, she quickly realizes she needs the help of her foe-turned-ally, archaeologist Nora Kelly, who soon uncovers a startling truth: the deceased had been poisoned, and died clutching a priceless artifact from outside High Lonesome.